PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK TWO STAY TWO STRAY TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 BAYANG - Andra, Mardisa - (STKIP PGRI Sumbar, 2014)
The research was motivated by the studentsâ comprehension of mathematic concept are still low at SMPN 1 Bayang. This research aims to determine the studentsâ comprehension of mathematic concept that apply Two Stay Two Stray better than studentsâ comprehension of mathematic concept that apply conventional learning in class VIII SMPN 1 Bayang. The type of research is experimental by using Randomized Control Group Only Design. The data analysis technique used is T-Test one part the help of MINITAB. The result of hypothesis test obtained P-Value = 0,027 is less than Î± = 0,05, then the hypothesis in this research received. In conclusion, studentsâ comprehension of math concept that apply Two Stay Two Stray type better than studentsâ comprehension of mathematic concept that apply conventional learning.